Knowledge domains and emerging trends of microglia research from 2002 to 2021: A bibliometric analysis and visualization study - Liu, Guangjie; Li, Tianhua; Yang, Anming; Zhang, Xin; Qi, Songtao; Feng, Wenfeng (Frontiers in Aging Neuroscience, 2023)
Background: Microglia have been identified for a century. In this period, their ontogeny and functions have come to light thanks to the tireless efforts of scientists. However, numerous documents are being produced, making it challenging for scholars, especially those new to the field, to understand them thoroughly. Therefore, having a reliable method for quickly grasping a field is crucial. Methods: We searched and downloaded articles from the Web of Science Core Collection with "microglia" or "microglial" in the title from 2002 to 2021. Eventually, 12813 articles were located and, using CiteSpace and VOSviewer, the fundamental data, knowledge domains, hot spots, and emerging trends, as well as the influential literature in the field of microglia research, were analyzed. Results: Following 2011, microglia publications grew significantly. The two prominent journals are Glia and J Neuroinflamm. The USA and Germany dominated the microglia study. The primary research institutions are Harvard Univ and Univ Freiburg, and the leading authors are Prinz Marco and Kettenmann Helmut. The knowledge domains of microglia include eight directions, namely neuroinflammation, lipopolysaccharide, aging, neuropathic pain, macrophages, Alzheimer’s disease, retina, and apoptosis. Microglial phenotype is the focus of research; while RNA-seq, exosome, and glycolysis are emerging topics, a microglial-specific marker is still a hard stone. We also identified 19 influential articles that contributed to the study of microglial origin (Mildner A 2007; Ginhoux F 2010), identity (Butovsky O 2014), homeostasis (Cardona AE 2006; Elmore MRP 2014); microglial function such as surveillance (Nimmerjahn A 2005), movement (Davalos D 2005; Haynes SE 2006), phagocytosis (Simard AR 2006), and synapse pruning (Wake H 2009; Paolicelli RC 2011; Schafer DP 2012; Parkhurst CN 2013); and microglial state/phenotype associated with disease (Keren-Shaul H 2017), as well as 5 review articles represented by Kettenmann H 2011. Conclusions: Using bibliometrics, we have investigated the fundamental data, knowledge structure, and dynamic evolution of microglia research over the previous 20 years. We hope this study can provide some inspiration and a reference for researchers studying microglia in neuroscience.